How do primary pupils give written arguments in a conflicting mathematical situation - Pehkonen, Leila (NOMAD Nordic Studies in Mathematics Education, 2000)
This paper deals with the written arguments primary pupils (N=201) gave when they faced a conflicting situation with confusing mathematical information. The theoretical framework is derived from the idea that mathematical argumentation is regulated by normative aspects. Both quantitative and qualitative methods were used in the analysing of the data. The results of this study suggest that although most pupils are able to give correct answers, many of them use mathematically irrelevant norms in their argumentation.